Three-Dimensional Scalar Time-Dependent Photorefractive Beam Propagation Model - Mark Cronin-Golomb (Photonics)
This paper presents an open-source time-dependent three-dimensional scalar photorefractive beam propagation model (PRProp3D) based on the well-known split-step method. The angular spectrum method is used for the diffractive steps, and the nonlinearities accumulated at the end of each diffractive step are applied using spatially varying phase screens. Comparisons with previously published experimental results are given for image amplification, photorefractive amplified scattering (fanning) and photorefractive screening solitons. Artifacts can be mitigated by use of step sizes less than 5~10 micrometers and by careful choice of the transverse computation grid size to ensure adequate sampling. Wraparound effects associated with the use of discrete Fourier transforms are mitigated by apodization and beam centering.